Hierarchically Nanoporous Bioactive Glasses for High Efficiency Immobilization of Enzymes. (23rd December 2013) - He, Wen; Min, Dandan; Zhang, Xudong; Zhang, Yang; Bi, Zhiying; Yue, Yuanzheng
<x xml:space="preserve">Abstract</x> Bioactive glasses with hierarchical nanoporosity and structures have been heavily involved in immobilization of enzymes. Because of meticulous design and ingenious hierarchical nanostructuration of porosities from yeast cell biotemplates, hierarchically nanostructured porous bioactive glasses can provide a simple, cost‐effective way to enhance catalytic activity of directly immobilized enzyme. Its unique chemical surface properties and hierarchical meso/macroporous structures lead to highly efficient catalytic performances of the directly immobilized enzymes. The enzyme molecules were spontaneously entrapped into the highly curved macropores (200–500 nm) via multipoint metal ion binding in electrical double layers. Hence, the enzyme activity and enzyme loading were enhanced, the cost of enzyme use was reduced, showing higher thermal and storage stabilities than free enzyme. The reactant and products of catalytic reactions can freely diffuse through open mesopores (2–40 nm). The formation mechanism of hierarchically structured porous bioactive glasses, the immobilization mechanism of enzyme and the catalysis mechanism of immobilized enzyme are then discussed. The novel nanostructure with advanced properties is expected to be utilized as a solid support for any enzyme for bioconversion, bioremediation, biosensors and drugs.